Prevalence of HIV infection and predictors for syphilis infection among female sex workers in southern China. - Lu, Fan; Jia, Yujiang; Sun, Xinhua; Wang, Lan; Liu, Wei; Xiao, Yan; Zeng, Gang; Li, Chunmei; Liu, Jianbo; Cassell, Holly; Chen, Huey T; Vermund, Sten H (The Southeast Asian journal of tropical medicine and public health, 2009)
The purpose of this study was to assess the prevalence and risk factors for syphilis infection among female sex workers (FSWs) in Liuzhou City, Guangxi Zhuang Autonomous Region, southern China. A cross-sectional study recruited FSWs using a venue-based method and subsequent snowball sampling with mapping strategies. Questionnaire-based interviews were conducted to collect demographic and behavioral information. Blood was tested for syphilis (RPR with TPPA confirmation) and HIV (EIA with Western blot confirmation) infections. Of the 362 eligible participants, 81.7% were non-local residents (60.5% from other parts of Guangxi and 21.2% were non-Guangxi residents); 58.0% belonged to non-Han minority ethnic groups; 37.5% reported inconsistent condom use with their clients and 71.2% reported inconsistent condom use with their regular sex partners during the past month. Nearly 10% reported having had sex with drug users. The prevalence rates for HIV and syphilis infections were 2.3% and 11.0%, respectively. Almost half (46.6%) of participants reported having had STD symptoms. Inconsistent condom use with clients in the past month (AOR = 5.0; 95% CI = 1.8-13.8), less education (OR = 2.6; 95% CI = 1.1-7.4), and HIV infection (AOR = 8.1; 95% CI = 1.1-68.5) were independently associated with syphilis infection.
Keywords: Adult; China; Cross-Sectional Studies; Disease Transmission, Infectious; Female; HIV Infections; HIV-1; Humans; Logistic Models; Multivariate Analysis; Prevalence; Prostitution; Questionnaires; Risk Factors; Sexual Behavior; Sexually Transmitted Diseases; Syphilis; Unsafe Sex